Pengembangan Bahan Ajar Kompilasi Fisika Matematika II Pokok Bahasan Persamaaan Diferensial Untuk Meningkatkan Penalaran Matematis - I Wayan Gunada; Joni Rokhmat; Hikmawati Hikmawati; Kesipudin Kesipudin (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to develop and produce teaching materials compilation of mathematical physics II on the subject of differential equations. Teaching materials that have been developed in the form of teaching modules. The research method used is a development study consisting of four stages: the stage of determination, design, development, and disseminate. The results obtained from this research are in the form of teaching module of mathematical physics II differential equation and its application. The teaching module generated in terms of feasibility aspects of content, presentation, and linguistics obtained amean score is 92.5 with a percentage is 79.74%. This shows that the teaching module that has been created as good and feasible to use. It can be categorized effective as measured by the impact of student activities, responses, and value of students reasoning abilities. The impact of student activity seen during the learning process after using the module is 73.59% and the student activity is categorized much or quite practical. The percentage of students' response after using the module was 80.1% and categorized well. The impact on the mathematical reasoning ability meanscore of the class 70.87.ÃÂ  This shows that the teaching module that has been created can beÃÂ  categorizedeffetive. Thus, it can be concluded that the teaching module compilation of mathematical physics II the subject of differential equations and their applications can be said to be effective and feasible to use.